2023
DOI: 10.1039/d3nr00681f
|View full text |Cite
|
Sign up to set email alerts
|

Giant coercivity enhancement in a room-temperature van der Waals magnet through substitutional metal-doping

Abstract: FexGeTe2 (x = 3, 4, 5) systems, two-dimensional (2D) van der Waals (vdW) ferromagnet (FM) metals with high Curie temperature (TC), have been intensively studied to realize all-2D spintronic devices....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 30 publications
0
3
0
Order By: Relevance
“…Moreover, as the magnetic properties of Fe 3 GeTe 2 , such as the T C , MAE, and coercive field, are reported to be sensitive to doping, we present the dependence of the magnetic properties of Fe 3 GaTe 2 on the chemical potential shift. This is important in potential device applications because the weak vdW interaction between layers allows the chemical potential to be changed by gating for thin film Fe 3 GaTe 2 . , …”
mentioning
confidence: 99%
“…Moreover, as the magnetic properties of Fe 3 GeTe 2 , such as the T C , MAE, and coercive field, are reported to be sensitive to doping, we present the dependence of the magnetic properties of Fe 3 GaTe 2 on the chemical potential shift. This is important in potential device applications because the weak vdW interaction between layers allows the chemical potential to be changed by gating for thin film Fe 3 GaTe 2 . , …”
mentioning
confidence: 99%
“…Here, the calculated c -axis lattice parameter of FCGT is 16.1323 Å, slightly lower than the pristine FGT ( c = 16.1897 Å) (Table S1, Supporting Information). The decrease of the c -axis lattice parameter with increasing doping level has also been observed in Ni doped Fe 3 GaTe 2 , which may be caused by the smaller ionic radius of doped ions. As shown in Figure a, this crystal structure consists of layered building blocks stacking along the c -axis, and each of these blocks contains a Fe/Co–Ga slab sandwiched between two Te layers.…”
mentioning
confidence: 74%
“…16 Additionally, it has been reported that Ni with x = 0.03 substituting for Fe in (Fe 1− x Ni x ) 3 GaTe 2 crystals can enhance the coercive field ( H C ) up to ∼200% while maintaining the ferromagnetic state at room temperature. 28 Despite these findings, there are still very few studies on substitutional doping of FGaT, especially on tuning antiferromagnetism. Thus, a systematic investigation into the effects of doping on the magnetic properties of FGaT is highly needed.…”
Section: Introductionmentioning
confidence: 99%